Neurocognitive development of memory for landmarks - Ekert, Janneke van; Wegman, Joost; Janzen, Gabriele (Frontiers in Psychology, 2015)
The capacity to detect landmarks in the environment and to associate each landmark with its spatial context is a fundamental operation for navigation, especially when the context is relevant for successful navigation. Recent evidence suggests robust age-related improvements in contextual memory. The current study investigated the effect of spatial context on landmark recognition memory in children and adolescents. Participants, ages 8 to 18, watched a video depicting a route through a virtual environment. The location at which landmarks occurred was manipulated to test the hypothesis that memory processes vary as a function of context. Functional magnetic resonance imaging data was acquired while participants performed an old-new recognition memory test of the landmarks. Old compared to new landmarks recruited a network of regions including the hippocampus and the inferior/middle frontal gyrus in all participants. Developmental differences were observed in the functional organization of the parahippocampal gyrus and the anterior cingulate cortex, such that memory representations strengthened linearly with age only when the associated spatial context was relevant for navigation. These results support the view that medial temporal lobe regions become increasingly specialized with development; these changes may be responsible for the development of successful navigation strategies.